2018
DOI: 10.1039/c7dt04392a
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective hydrosilylation of olefins and acetylenes by platinum(0) complexes bearing bulky N-heterocyclic carbene ligands

Abstract: Platinum complexes bearing bulky N-heterocyclic carbene (NHC) ligands, i.e., [Pt(IPr*)(dvtms)] (where, IPr* = 1,3-bis{2,6-bis(diphenylmethyl)-4-methylphenyl}imidazol-2-ylidene) and [Pt(IPr*OMe)(dvtms)] (where, IPr*OMe = 1,3-bis{2,6-bis(diphenylmethyl)-4-methoxyphenyl}imidazol-2-ylidene, dvtms = divinyltetramethyldisiloxane) catalyse nearly quantitatively and highly or completely the selective hydrosilylation of terminal olefins as well as terminal or internal acetylenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…[45] The scope of these tests are collected in Table 1. [45] The scope of these tests are collected in Table 1.…”
Section: ] and Based On Rh ([Rhcl(cod)] 2 [Rhcl(pph) 3 ]) And Ir ([Imentioning
confidence: 99%
See 1 more Smart Citation
“…[45] The scope of these tests are collected in Table 1. [45] The scope of these tests are collected in Table 1.…”
Section: ] and Based On Rh ([Rhcl(cod)] 2 [Rhcl(pph) 3 ]) And Ir ([Imentioning
confidence: 99%
“…As it was mentioned, we observed similar selectivities of β-hydrosilylation products when styrenes were used, analogously to monosubstituted silsesquioxanes and regardless of the catalyst used. [45] This observation could be explained by the polarizing effect of the phenyl group at vinyl moiety. 20 h, due to lower excess of styrenes (1.0125 equiv.…”
Section: ] and Based On Rh ([Rhcl(cod)] 2 [Rhcl(pph) 3 ]) And Ir ([Imentioning
confidence: 99%
“…We have recently demonstrated that hydrosilylation of terminal olefins as well as terminal and internal acetylenes catalyzed by platinum(0) complexes containing highly hindered NHC ligands occurs with complete regio‐ and stereoselectivity (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
“…Hydrosilylation of olefins and acetylenes with trisubstituted silanes presented in our previous paper. Reproduced from ref …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation